Improving Students' Critical Thinking Skills through a Deep Learning-Oriented Group Investigation Model - Zulfani Nurdiana Agustin; Sifak Indana; Nadi Suprapto (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This research aims to improve the critical thinking skills of junior high school students through the application of the Group Investigation cooperative learning model oriented to deep learning on the interaction of living things and their environment. Methodology: This study uses a quantitative approach with a quasi-experimental design of one group pretest-posttest multiple groups. The subject of the study is the students of grade VII of junior high school which consists of two classes. Data was collected through observation of students’ learning implementation and activities, critical thinking skills tests, and student response questionnaires, then analyzed using percentage, N-gain, Wilcoxon test, and effect size. Main Findings: The main findings of this study show that the application of the Group Investigation cooperative learning model oriented to deep learning is able to strengthen the critical thinking skills of junior high school students significantly and meaningfully. The integration of deep learning approaches at each stage of investigation encourages a high level of cognitive engagement through the process of analysis, evaluation, and conceptual reflection. Novelty/Originality of this study: The Group Investigation model in general, this study presents a novelty in the form of integrating a deep learning approach into each stage of GI to encourage the process of analysis, evaluation, and conceptual reflection of students, so that the improvement of critical thinking skills does not only occur quantitatively, but also in every critical thinking indicator.